HIV testing: getting the message across—a survey of knowledge, attitudes and practice among non-HIV specialist physicians. Issue 1036 (15th December 2011) - Hunter, Ewan; Perry, Meghan; Leen, Clifford; Premchand, Nikhil
Abstract : Introduction: 26% of people living with HIV in the UK remain undiagnosed and over 50% of adults with HIV are significantly immunocompromised at the time of diagnosis. Current guidelines recommend routine testing in all patients presenting with a range of conditions in low prevalence areas (<2/1000). Methods: The authors conducted an online survey of the knowledge, attitudes and practice of non-HIV specialist physicians with regard to HIV testing in two areas of the UK with a lower prevalence of HIV. Key outcomes included recognition of recommended clinical indications for HIV testing and perceived barriers to performing HIV tests more routinely. All responses were collected in July 2009. Results: Recommended indications for HIV testing were identified by 0–43.7% of 119 respondents. 47.9% cited a low prevalence of HIV as a barrier to routine testing. 88% of 60 consultant physicians were unaware of current guidelines on testing for HIV. Conclusion: The authors found a low awareness of current guidance on testing for HIV and a high level of perceived barriers to testing. Reducing the high number of late diagnoses is a clinical and public health priority. To achieve this, the authors recommend improved policy dispersal coupled with education that targets perceived barriers to testing.